2021
DOI: 10.1016/j.rmed.2021.106603
|View full text |Cite
|
Sign up to set email alerts
|

Adult but not childhood onset asthma is associated with the metabolic syndrome, independent from body mass index

Abstract: Adult-onset asthma (AOA) is usually more severe compared to childhood onset asthma (CoA). Given the increasing evidence that AoA is associated with obesity, we investigated the relationship of other related metabolic comorbid conditions with AoA compared to CoA. Study design and methods: This cross-sectional study compared the metabolic syndrome and lipid derived inflammatory markers in patients with AoA, CoA and age-and sex-matched control subjects without asthma. Participants were asthma patients visiting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…We showed significant positive correlations in age, gender, race, hypertension, diabetes and presence of blood relatives with asthma subgroups, which also indicates the prevalence of METS-IR index use for asthma population. Furthermore, we observed that increasing age, females, hypertensive, and diabetic populations have higher prevalences, which is in accordance with previous findings ( 12 , 22 25 )…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We showed significant positive correlations in age, gender, race, hypertension, diabetes and presence of blood relatives with asthma subgroups, which also indicates the prevalence of METS-IR index use for asthma population. Furthermore, we observed that increasing age, females, hypertensive, and diabetic populations have higher prevalences, which is in accordance with previous findings ( 12 , 22 25 )…”
Section: Discussionsupporting
confidence: 93%
“…We showed significant positive correlations in age, gender, race, hypertension, diabetes and presence of blood relatives with asthma subgroups, which also indicates the prevalence of METS-IR index use for asthma population. Furthermore, we observed that increasing age, females, hypertensive, and diabetic populations have higher prevalences, which is in accordance with previous findings (12,(22)(23)(24)(25) According to epidemiological studies, asthma is a heterogeneous disease, and there are several clinical subgroups depending on age of onset, duration of disease, and clinical features (26). Literature indicates that the longer a person suffers from asthma, the more likely they are to decline in respiratory function and their prognosis will be adverse (27).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of metabolic syndrome is elevated in asthma patients [ 53 ]. Although the correlation between asthma and metabolic syndrome needs to be cleared, it may be influenced by various factors, including high BMI, increased resistin levels, dyslipidemia, and mitochondrial dysfunction [ 54 , 55 , 56 ].…”
Section: Clinical Overlap Between Asthma and Pcosmentioning
confidence: 99%
“…The prevalence of metabolic syndrome among patients with asthma is estimated to be 25% [ 91 ]. A recent study has shown that metabolic syndrome is more prevalent in asthma patients compared to controls, and that the onset of asthma in adulthood is associated with metabolic syndrome, even when adjusted for age, sex, body mass index and smoking history [ 92 ]. Among the components of metabolic syndrome, two are mainly associated with an increased risk of incident asthma in adults: high waist circumference and elevated glucose or diabetes.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%